1994
DOI: 10.1111/j.1365-3148.1994.tb00241.x
|View full text |Cite
|
Sign up to set email alerts
|

Discharge haematocrit as clinical indicator for blood transfusion audit in surgery patients

Abstract: Three cohorts of elective surgical patients were reviewed in order to develop a method in which the discharge haematocrit can serve as a clinical indicator for a subsequent study of the use of blood transfusion therapy. Three different levels of discharge haematocrit were evaluated: 36, 33, and 30% for 'generous', 'intermediate', and 'strict' criteria, respectively. Discharge haematocrits (%, mean +/- SD) for patients not transfused were 29.6 +/- 4.6, 33.7 +/- 5.0, and 33.6 +/- 3.4 for three different surgical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…A more practical approach is to study outcomes rather than the process by which the decision is made. Goodnough et al 21 suggested that discharge haemoglobin is a relevant and practical outcome to measure the appropriateness of red cell transfusion. In the current study, discharge haemoglobin values suggested that 50% of women were transfused to a haemoglobin of >10 g/dL, the highest being 13.1 g/dL.…”
Section: Discussionmentioning
confidence: 99%
“…A more practical approach is to study outcomes rather than the process by which the decision is made. Goodnough et al 21 suggested that discharge haemoglobin is a relevant and practical outcome to measure the appropriateness of red cell transfusion. In the current study, discharge haemoglobin values suggested that 50% of women were transfused to a haemoglobin of >10 g/dL, the highest being 13.1 g/dL.…”
Section: Discussionmentioning
confidence: 99%
“…A more practical approach is to study an outcome rather than the process by which the decision is made. Goodnough et al . (1994) have suggested that discharge haemoglobin is a relevant and practical outcome measure with direct applicability to red cell transfusion.…”
Section: What Standards To Audit Againstmentioning
confidence: 99%
“…The discharge hematocrit level is useful with respect to understanding transfusion outcomes retrospectively, [29] but prospective clinical indicators are necessary if physician transfusion behavior is to be altered. One promising approach in patients about to undergo cardiac surgery is to guide the decision-making process by coupling the use of algorithms for the transfusion of blood and blood components with readily available clinical information obtained from point-of-care testing, which is generally not possible with laboratory-based assays.…”
Section: Transfusion Algorithmsmentioning
confidence: 99%